Buffett’s alpha: further explanations from a behavioral value investing perspective - Otuteye, Eben (Springer Nature, 2020)
Warren Buiett has had extraordinary success as an investor, but there is no agreement as to why. Some academic researchers attribute his performance to mere luck. Frazzini etfal. (Financ Anal J 74(4):35– 5, 2018), concluded that his alpha is due to leveraging safe, high- quality, and cheap stocks. However, there has been no analysis to date of Buiett’s performance from a behavioral perspective. We argue that Buiett’s success is partly due to qualitative and psychological factors, including tenacity, patience, avoidance of overconldence, organizational culture, and the reputation eiect. Using information from shareholder letters, writings, interviews, and speeches by Buiett and his colleague Charlie Munger, we demonstrate how such  psychological factors, together with the quantitative lndings of Frazzini etfal., render a more complete and satisfying explanation of Buiett’s alpha.